(untitled) (Libellarium: journal for research in the field of information and related sciences, 2013)
The aim of this paper is to describe and critically analyse the application of citation analysis in the collection evaluation in academic libraries, and to present the results of the study. The study, first of its kind in Croatia, was carried out in the information sciences collection at the Faculty of Humanities and Social Sciences in Osijek. Based on many studies from abroad done in the academic environment, the citation analysis, despite its disadvantages, proved to be a valid method for the collection of indicators of real use of (library) information sources. The study analysed citation patterns, characteristics of information sources used by respondents and the accessibility of these sources in the academic library. Its aim was also to test the method of citation analysis in the context of library collection evaluation. The samples used in this study were papers published in 2010 by the students and teachers of the Department of Information Sciences in Osijek. The data analysis showed that while students preferred electronic information sources, teachers preferred print sources. Also, periodicals and monographs were top two information types used in the compilation of studied publications. However, students used undefined type of web resources such as presentations and commercial and educational websites to a great extent. As far as accessibility of sources used is concerned, the results show that library offers access to 60% of periodicals used and approximately 25% of monographs. In order to minimize the limitations of this quantitative method and to obtain valid and reliable indicators of citation patterns and use of (library) information sources by students and teachers at the given Department, this study should be carried out longitudinally. It should also be complemented with a qualitative study (e.g. interview with teachers and students).